A comparison of results after arthroscopic anterior cruciate ligament reconstruction in female and male competitive athletes. A two- to five-year follow-up of 429 patients - Wiger, P.; Brandsson, S.; Kartus, J.; Eriksson, B. I.; Karlsson, J. (Scandinavian Journal of Medicine & Science in Sports, 1999)
The aim of this study was to compare the results after arthroscopic anterior cruciate ligament reconstruction in female and male competitive athletes who had a pre-injury Tegner activity level of > or =7 and a non-injured contralateral anterior cruciate ligament. One hundred and thirty-three female and 296 male patients were followed at 38 (21-68) months after the index operation. All the patients were operated on by experienced knee surgeons using patellar tendon autografts and interference screw fixation. At the index operation the median age of the female patients was 23 (1645) years and the median age of the male patients was 26 (16-47) years. The reconstruction was performed a median of 10 (0-141) and 10 (0-203) months after the injury in women and men respectively. The patients were re-examined by independent observers. At the follow-up, the median Lysholm score was 89 (38-100) points in the female group and 90 (22-100) points in the male group (P=0.015). The IKDC evaluation system, subjective anterior knee pain, subjective evaluation of the results, the knee-walking test and the KT-1000 tests revealed no differences between the groups. The mean (+/-2 SD) pre-injury Tegner activity level was 8.1 (+/-1.9) (median 8 (7-10)) in the female group and 8.4 (+/-1.8) (median 9 (7-10)) in the male group (P=0.003). At the follow-up, the Tegner activity level was 6.2 (+/-3.8) in the female group and 6.8 (+/-3.6) in the male group (P=0.012). At the follow-up, the Tegner activity level had decreased by 1.9 (+/-3.8) for the women and 1.6 (+/-3.3) for the men, as compared with the pre-injury level (n.s.). The difference between the performed and the desired activity level at the follow-up was 1.1 (+/-3.2) in the female group and 0.9 (+/-3.0) in the male group (n.s.). In the female group 53/133 (40%) and in the male group 115/296 (39%) returned to the pre-injury activity level (n.s.). The median one-leg-hop quotient was 93 (0-116)% in the female group and 96 (0-130)% in the male group (P=0.006). Concomitant meniscal injuries prior to the index operation, at the index operation or during the follow-up period were found in 64/133 (48%) women and in 185/ 296 (62%) men (P<0.01). The main conclusion was that the overall results in female and male athletes were comparable two to five years after the anterior cruciate ligament reconstruction. However, concomitant meniscal injuries were more common in male than females athletes after anterior cruciate ligament injuries. Scand J Med Sci Sports 1999 Oct;9(5):290-5